Developing International Agricultural Communications: A Photo Elicitation of International Agricultural Development Implementors - Lacey Roberts-Hill; Elia Rybolt; Delice Twahirwa; Tobin Redwine; Tracy Rutherford; Kim E Dooley; Joyce Elaine Juntune; Elsa Murano (Journal of International Agricultural and Extension Education, 2026)
Changes in stakeholders in international agricultural development create new needs for communication channels to facilitate knowledge transfer. It is crucial to address this gap between program needs and program success for development programs to thrive. As communication is measured, visually communications need to be addressed specifically. Visual communication is needed to bridge the gap between local communities and implementing programmers. Using photo elicitation, researchers purposively sampled individuals who were program directors, agricultural development practitioners, and program implementors in Farmer-to-Farmer programs in Bangladesh, Nepal, Egypt and Lebanon. Findings were grouped to identify four main elements desired by program practitioners and beneficiaries to help communicate about international agricultural development. These included contextual, compositional, humanizing, and engaging elements. The four elements discovered should be considered factors in a model of international agricultural development communication and implemented to align practitioners’ views of programs with other stakeholders in the system.
Keywords: photo elicitation; development communication; visual literacy